Accounting Devices and Fiscal Illusions - Irwin, Timothy (Staff Discussion Notes; Staff Discussion Notes, 2012)
This proposed SDN surveys the various accounting stratagems which governments have used to meet fiscal targets-thereby sidestepping the need for true adjustment-and suggests remedial actions to limit this type of fiscal non-transparency. Types of creative accounting covered includes, for instance, currency swaps to hide a debt build-up (as in Greece in 2001-07), sale and leaseback of government property (for example, in the United States), assumption of long-term pension obligations in exchange for short-term revenue (Argentina, Hungary, and other Eastern European countries), use of public-private partnerships to defer the recognition of investment spending (for instance, Portugal), and reliance on non-cash compensation (such as pension rights) to reduce measured wage bills (in the United States, United Kingdom, et cetera) As is evident from the examples given, these fiscal tricks have recently come under increased international scrutiny, highlighting the importance of good fiscal reporting, accounting, and transparency in general, for avoiding unpleasant surprises, ensuring government accountability, and containing fiscal vulnerabilities.